2009
DOI: 10.1158/0008-5472.can-08-4466
|View full text |Cite
|
Sign up to set email alerts
|

GPR109A Is a G-protein–Coupled Receptor for the Bacterial Fermentation Product Butyrate and Functions as a Tumor Suppressor in Colon

Abstract: Short-chain fatty acids, generated in colon by bacterial fermentation of dietary fiber, protect against colorectal cancer and inflammatory bowel disease. Among these bacterial metabolites, butyrate is biologically most relevant. GPR109A is a G-protein-coupled receptor for nicotinate, but recognizes butyrate with low affinity. Millimolar concentrations of butyrate are needed to activate the receptor. Although concentrations of butyrate in colonic lumen are sufficient to activate the receptor maximally, there ha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
525
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 607 publications
(534 citation statements)
references
References 38 publications
7
525
1
1
Order By: Relevance
“…Similarly, absence of GPR109A in the non-haematopoeitic compartment abrogated the protective effects of fibre in DSS colitis ( Supplementary Fig. 5), presumably in the epithelium, a site of GPR109A expression 22 .…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…Similarly, absence of GPR109A in the non-haematopoeitic compartment abrogated the protective effects of fibre in DSS colitis ( Supplementary Fig. 5), presumably in the epithelium, a site of GPR109A expression 22 .…”
Section: Resultsmentioning
confidence: 73%
“…3b). Because GPR43 did not account for 100% of the beneficial effects of a high-fibre diet, at least by clinical score, we next tested GPR109A, a receptor expressed by colonic epithelial cells 22 that binds the SCFA butyrate and the fatty acid-derived ketone body (D)-beta-hydroxybutyrate 23 . We found that protection in the DSS model provided by high-fibre diet was GPR109A dependent, at least by clinical scores (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Short‐chain fatty acids have potent immunomodulatory activities on intestinal dendritic cells and lymphocytes as shown by the enhancement of gut T‐regulatory cell development with mixtures or specific species of Clostridiales that decreased colitis and systemic IgE responses in an experimental animal models (Thangaraju et al. 2009; Berdnt et al. 2012; Furusawa et al.…”
Section: Discussionmentioning
confidence: 99%
“…SLC5A8 has been shown to function as a tumor suppressor in the colon (17) and other tissues (13,18,19); the ability of this transporter to mediate the Na ϩ -coupled entry of HDAC inhibitors (butyrate, propionate, and pyruvate) into cells underlies the tumor-suppressive function of this transporter (15,16). While SLC5A8 is necessary for the intracellular actions of butyrate, butyrate also elicits biologic effects on colon cells extracellularly by serving as an agonist for the cell surface G-protein-coupled receptor GPR109A, but without involving HDAC inhibition (20). GPR109A was originally described as the receptor for nicotinate, and the acti-vation of the receptor by nicotinate provided the molecular basis for the anti-lipolytic actions of this vitamin (21,22).…”
Section: Dendritic Cells (Dcs)mentioning
confidence: 99%
“…Subsequent studies have shown that the ketone body ␤-hydroxybutyrate is the physiologic ligand for the receptor (23). Butyrate is also able to activate the receptor but with a low affinity; millimolar concentrations of butyrate are needed to activate the receptor (20,23). This indicates that butyrate might serve as a ligand for GPR109A in the colon under physiologic conditions because of the presence of high levels of this fatty acid in the colonic lumen (ϳ20 mM) due to bacterial fermentation of dietary fiber.…”
Section: Dendritic Cells (Dcs)mentioning
confidence: 99%